Pendampingan Health Promoting School Terintegrasi di SMP PGRI 01 Kota Batu - Masruroh, Nur Lailatul; Kurnia, Anggraini Dwi; Melizza, Nur (University of Merdeka Malang, 2020)
Health complaints in high school children are dizziness, stomachache and fever. Problems related to the psychology of students get treatment from teachers, while for physical health problems usually done by the school is sending students home or delivering them to the nearest health center. The integrated Health Promoting School Initiation aim to reactivate the role of UKS. This effort is integrated with the role of the Guidance Counseling (BK) unit. The purpose was to provide integrated Health Promoting School assistance in SMP PGRI 01 Kota Batu. The problem-solving method was activating and training for UKS cadres. Community Service activities carried out in SMP PGRI 01 Kota Batu, from preparation, licensing to evaluation, were conducted in the period of April - September 2019. The activities went well, all training participants consisting of students and teachers followed the activities from beginning to end, as shown from the significant differences from the pre-test and post-test results. Posttest value indicates 100% there is an increase in value. Follow-up of activities that have been carried out in the form of community service programs that will further strengthen the programs that have been initiated in the current program and develop to solve the following problems.DOI:Â https://doi.org/10.26905/abdimas.v5i2.3986